On a minimization technique using interval mathematics - Ishak Ahmad, (Universiti Kebangsaan Malaysia, 2002)
In this paper we adapt to the interval Newton method the transformation-invariant descent-direction strategy which can be used to address the problem of minimizing nearly-singular systems of equations. We show that the modified interval Newton method performed better than the classic interval Newton method.